Micropattern‐Controlled Cell Density and Its Effect on Gene Transfection of Mesenchymal Stem Cells. Issue 18 (27th January 2022) - Wang, Yongtao; Yoshitomi, Toru; Kawazoe, Naoki; Yang, Yingnan; Chen, Guoping
Abstract: Influence of cell density on gene transfection and the underlying mechanism remain unclear. In this study, micropatterned surfaces are prepared to control cell density, cell morphology, and cell–cell interactions to investigate how and why cell density affects gene transfection of mesenchymal stem cells. Cell density is controlled by adjusting the ratio of cell adhesive area to nonadhesive area. Gene transfection is dependent on cell density. A moderate cell density is beneficial for gene transfection, while low (2.5 ± 0.7 × 10 3 cells cm −2 ) and high (112.6 ± 9.6 × 10 3 cells cm −2 ) cell densities have negative effects on transfection. Influence of cell density on gene transfection is strongly correlated with its influence on cellular uptake capacity and DNA synthesis. High cellular uptake and DNA synthesis promote gene transfection. Variations in cell morphology and cell–cell interaction levels of populations with different cell densities could explain the influence of cell density. Large cell size (low cell density) and strong cell–cell interaction (high cell density) could increase gene transfection. Cell protrusion of large cells could slightly promote gene transfection. Balance of these factors is important for maximal gene transfection. The results should be useful for understanding the effect of cell density on gene transfection. Abstract : Micropatterns are used to control cell density and the influence of cell density on gene transfection is disclosed. Cell density could affect transfection efficiency through the regulation of cell size, cell protrusion, and cell–cell interaction. Its influence is strongly correlated with cellular uptake capacity and DNA synthesis activity.